CYP2C19*2 Polymorphism Is Associated with Impaired Oral Clearance of Gliclazide in Healthy Chinese - Chow E; Poon EWM; Fok BSP; Chan JCN; Tomlinson B (Dove Medical Press, 2020)
Elaine Chow,1,2 Emily WM Poon,2 Benny SP Fok,1 Juliana CN Chan,2 Brian Tomlinson1–3 1Phase 1 Clinical Trial Centre, The Chinese University of Hong Kong, Hong Kong; 2Department of Medicine and Therapeutics, The Chinese University of Hong Kong, Hong Kong; 3Faculty of Medicine, Macau University of Science & Technology, Taipa, MacauCorrespondence: Elaine Chow Email e.chow@cuhk.edu.hkBackground: Previous studies suggest gliclazide is metabolised primarily by CYP2C19 rather than CYP2C9, unlike other sulphonylureas. CYP2C19 *2 and *3 polymorphisms are more common in Asians.Methods: We investigated the effect of CYP2C19 polymorphisms on gliclazide pharmacokinetics in 15 healthy male Chinese subjects after a single 80mg oral dose.Results: In CYP2C19 poor metabolisers (*2/*2, n=4), plasma area-under-the-curve was higher by nearly two-fold compared with intermediate metabolisers (*2 and *3 heterozygotes, n=7) and extensive metabolisers (*1/*1, n=4) (p<0.001). Apparent oral clearance was mean (SD) 0.70 (0.12), 1.22 (0.22) and 1.52 (0.47) mL/min/kg in poor, intermediate and extensive metabolisers, respectively (p = 0.005).Conclusion: CYP2C19*2 polymorphism is associated with increased total gliclazide concentration and reduced oral clearance. Pharmacogenetic studies are warranted on the impact of CYP2C19 polymorphisms on treatment response and hypoglycaemia.Keywords: gliclazide, pharmacogenetics, CYP2C19